Determination of fracture toughness in plain concrete specimens by R curve - Chbani Hamza; Saadouki Bouchra; Barakat Mohamed (Fracture and Structural Integrity)
Experimental tests and computational algorithm are implemented to investigate crack growth phenomena in C0.7 concrete. Firstly, three point bending tests are carried out on normalized prismatic specimens notched laterally (SENB), then, computational calculation was developed to calculate the concrete toughness on the basis of R-curve method. The R-curve was obtained from the curve connecting the crack mouth opening displacement (CMOD) to the applied load. During loading, elastic deformation followed by a significant plastic deformation were observed. Therefore, the crack growth in C0.7 concrete is defining by three stages: crack initiation, stable crack propagation and an unstable fracture. The average value of the critical stress intensity factor for the C0.7 concrete is 1.05 MPa.m1/2.